Mass Balance Analysis of Bioethanol Production from Petai Peel (Parkia speciosa) through Enzymatic Process - Erwan Adi Saputro; Rachmad Ramadhan Yogaswara; Nerissa Arviana; Luckyana Aini; A.R Yelvia Sunarti; Reva Edra Nugraha (International Journal of Eco-Innovation in Science and Engineering, 2021)
The consumption of fuel for transportation is increasing during the last decade. Bioethanol is one of the renewable energy has a good opportunity to be applied when the lack of fossil fuel. Bioethanol is derived from the lignocellulose substance through a fermentation process. In this research, the lignocellulose came from the petai peel (Parkia speciosa). The peel was hydrolyzed using an enzyme and continuously fermented for 5 days. The aim of this research is to analyst the mass balance of the bioethanol production from petai peel (Parkia speciosa) through the enzymatic process. The enzyme used in this research are alfa amylase (10 ml) and glucoamylase (10 ml), also Saccharomyces cerevisiae used in the fermentation process. The result shows that the initial material of petai peel was 57 grams will produce bioethanol around 14 grams.